POTENTIAL OF THE BIOMOLECULES FOR GAS HYDRATE INHIBITION IN FLOW ASSURANCE: COSMO-RS BASED ESTIMATIONS - Yaqub, S.; Adnan, A.; Lal, B.; Shah, A.H.; Murtaza, M. (Journal of Advanced Manufacturing Technology (JAMT), 2020)
The formation of gas hydrate causes a major flow assurance problem in petroleum industry. Conventional hydrate inhibitors such as, salts, Ionic liquids (ILs), polymers and amino acids are being used to overcome the issues. The usage of conventional hydrate inhibitors has certain limitations in term of low biodegradability and high operational cost. Biomolecules such as Pectin, Sodium-Carboxymethyl Cellulose (Na-CMC), Starch, Glycine and Dextran are some of the biodegradable polysaccharides that can be used as an alternative inhibitors. These biomolecules are complex long chain structures; therefore, before hydrate experiments, their fundamental properties are simulated by a software, Conductor-Like Screening Model for Real Solvents (COSMO-RS). Surface charge distribution, sigma potential, sigma profile and hydrogen-bonding energy of monomers with H2O, methane (CH4) and carbondioxide (CO2) is estimated. By working as a pre-screening tool, the software predicted that Na-CMC and Dextran have higher electropositive distribution. While Starch, Pectin and Glycine shows an almost equal distribution of electropositive and electronegative charges on their surfaces. Pectin, Glycine, Na-CMC and Dextran shows strong hydrogen-bonding with H2O molecules. Starch, on the other hands, shows less effective hydrogen-bonding activity with H2O.